An Analysis of Linguistic Features and Meaning in the Song Lyrics of “Cause You Have To” by LANY - Andini Khairunisa Sulaiman; Otong Setiawan Djauhari (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study aims to analyze the figurative language used in the song lyrics of “Cause You Have To” by the American band LANY. Using a qualitative descriptive method, this research identifies and interprets various types of figurative language found in the lyrics, focusing on metaphor, simile, hyperbole, personification, symbolism, irony, allusion, and synecdoche. The findings reveal that these figurative devices play a significant role in conveying the emotional depth, psychological tension, and relational conflict expressed in the song. Metaphors and hyperboles dominate the lyrics, enhancing the emotional impact by illustrating themes of unreciprocated love, emotional detachment, and inner turmoil. For example, metaphors like “the silence is getting too cold” and hyperbolic expressions such as “I’d drive through the night” contribute to the song’s emotional intensity. The study concludes that figurative language is essential in shaping the narrative and emotional resonance of the song, allowing listeners to engage with the lyrics on a more personal and interpretive level. This research highlights the importance of figurative language in music and its role in deepening the listener’s emotional experience.